538 Sleep and Self-Efficacy: The Role of Domain Specificity in Predicting Sleep. (3rd May 2021) - Ghose, Sarah; Dzierzewski, Joseph; MacPherson, Ashley; Sabet, Sahar; Williams, Claire; Reid, Morgan; Dautovich, Natalie
Abstract: Introduction: Poor sleep occurs across the lifespan and has a number of consequences across biopsychosocial life domains. As such, it is important to identify modifiable psychobehavioral mechanisms contributing to sleep disturbance as potential targets for research and intervention. Self-efficacy may play a significant role in sleep behavior outcomes. The present study aimed to determine the differential associations between general and sleep self-efficacy and sleep among a lifespan sample of adults. Methods: Data from the Investigating Sleep Longitudinally Across Normal Development (ISLAND) study were utilized for the present investigation. Participants were 3, 284 adults (48.5% female, 6.4% other-identifying, Mage= 43 yrs., SD=16.72 yrs.) who completed self-report sleep, general-, and sleep self-efficacy measures as part of their study involvement. A Structural Equation Model (SEM) was estimated to investigate whether general or sleep self-efficacy were significant predictors of a latent sleep disturbance variable, which was comprised of the presence of insomnia symptoms (Insomnia Severity Index) and the absence of sleep health (RU-SATED). Invariance tests were utilized to determine whether the model held across age and sex. Results: The structural model evidenced good fit to the data and indicated that general self-efficacy did not have a significant, direct impact on the latent sleep construct (b=-.01, p=.33); however, sleep self-efficacy did display a significant, negative association with sleep disturbance (b=-.82, p<.001), whereby increased sleep self-efficacy was associated lower levels of disturbed sleep. The model was largely invariant across age and sex. Conclusion: Sleep self-efficacy surfaced as an important predictor of sleep disturbance above and beyond general self-efficacy. Findings highlight the importance of domain specificity in the predicting sleep outcomes. Additionally, findings suggest the need for increased research into and application of interventions targeted toward increasing sleep self-efficacy in individuals with sleep disturbance as a potential avenue to improve sleep health. Support (if any):